Defying Rationality: Florensky and Frank - Drozdek, Adam (Wydział Teologiczny UAM, 2008)
Some philosophers and theologians state that there is a limit to rational reasoning beyond which experience or intuition should be used. Forceful arguments for the limitation of some logical principles are presented by Florensky and Frank. Some of their arguments are investigated in the present paper.
Przezwyciężyć racjonalność: Fiorenski i Frank